Real-time optical imaging of the hypoxic status in hemangioma endothelial cells during propranolol therapy - Wu, Yue; Yang, Xiaojuan; Zhai, Mingrui; Chen, Yi; Lu, Xiaoya; Ju, Jiandong; Zhang, Huanqing; Wang, Guanduo; Zhang, Zhe; Zhu, Baocun; Wang, Xuan; Chen, Zhanwei; et al. (Frontiers in Oncology, 2022)
Infantile hemangioma (IH) is the most common microvascular tumor of infancy involving the area of head and neck. One of the most important independent risk factors of IH is the hypoxia microenvironment. Fluorescent chemosensor provides a noninvasive intervention, high spatiotemporal resolution, ultrasensitive response, and real-time feedback approach to reveal the hypoxic status of cells. Our research group developed an ultrasensitive fluorescent chemosensor, HNT-NTR, and investigated the potential ability of imaging the hypoxic status of hemangioma-derived endothelial cells (HemECs). In this study, we successfully visualized the propranolol (PRN) treatment in HemECs using NHT-NTR with "Turn-off" sensing method. This chemosensor exhibited high sensitivity and selectivity for optical imaging of hypoxic status with fast responsiveness, real-time feedback and durable photostability of the fluorescent signal. It was also confirmed that HNT-NTR could monitor nitroreductase in vivo. Paramountly, we expected this chemosensor to offer an available optical method for imaging of the hypoxic status and visualizing the therapeutic status of PRN therapy in IH with the hypoxia-imaging capability.